ISSUES OF ASSESSING THE ROLE OF STRUCTURAL CHANGES OF THE ECONOMY IN ENSURING SMALL BUSINESS DEVELOPMENT (Marketing Journal, 2025)
In this paper developed models for assessing impact of structural changes in economy on number of registered and active small business entities in Navoi region. Carried a comparative analysis based determined of the elasticity coefficients defined by developed models , as well as assessed impact of changes in sectors . Also , presented results of assessing impact of sectors on activeness level of small business entities . Based on obtained results , identified perspectives for the development of small business in region.
Keywords: small business; structural structure of economy; model; ARMAX model; coefficient of determination; activeness level